Antibacterial Activity Test of Ethyl Asetate Fraction of Gletang Growth (Tridax procumbens L.) on The Growth of Enterococcus faecalis - Widyawati; Ulima Audia Fayi Arta; Okmes Fadriyanti (Denta Journal Kedokteran Gigi, 2026)
Background: Intractable root canal infection remains a serious obstacle in endodontic therapy and is a frequent cause of treatment failure, with Enterococcus faecalis (E. faecalis) as a key pathogen. This Gram-positive bacterium can persist under harsh conditions within the root canal system. Chlorhexidine is commonly used as a chemical irrigant, but its long-term application is associated with undesirable side effects, prompting the search for natural antibacterial alternatives. One promising candidate is the gletang plant (Tridax procumbens L.), which contains bioactive compounds with potential antimicrobial effects. Objective: This study aimed to evaluate the antibacterial activity of the ethyl acetate fraction of Tridax procumbens L. at various concentrations against E. faecalis. Method: A laboratory experimental design with post test only control group was used. Antibacterial testing was performed using the agar diffusion method with the gletang ethyl acetate fraction at 2%, 4%, 6%, and 8%, chlorhexidine as a positive control, and 96% methanol as a negative control. Data were analyzed univariately in tables and bivariately using Kruskal–Wallis and Mann–Whitney tests. Results: The fraction inhibited E. faecalis growth, with the largest mean inhibition zone of 3.6 mm at 8% and the smallest at 2%, 1.6 mm. Overall activity across all concentrations was classified as weak; however, statistical analysis (p=0.003, p<0.05) confirmed a significant inhibitory effect. Conclusion: The ethyl acetate fraction of the gletang plant (Tridax procumbens L.) at 8% is effective as an antibacterial against Enterococcus faecalis, with an average inhibition zone diameter close to that of the positive control. The higher the concentration of the ethyl acetate fraction, the higher the bacterial inhibition.